A data-driven computational scheme for the nonlinear mechanical properties of cellular mechanical metamaterials under large deformation. Issue 32 (23rd July 2020) - Xue, Tianju; Beatson, Alex; Chiaramonte, Maurizio; Roeder, Geoffrey; Ash, Jordan T.; Menguc, Yigit; Adriaenssens, Sigrid; Adams, Ryan P.; Mao, Sheng
Abstract : A novel computational scheme using neural networks is proposed to efficiently capture the nonlinear mechanics of soft metamaterials under large deformation. Abstract : Cellular mechanical metamaterials are a special class of materials whose mechanical properties are primarily determined by their geometry. However, capturing the nonlinear mechanical behavior of these materials, especially those with complex geometries and under large deformation, can be challenging due to inherent computational complexity. In this work, we propose a data-driven multiscale computational scheme as a possible route to resolve this challenge. We use a neural network to approximate the effective strain energy density as a function of cellular geometry and overall deformation. The network is constructed by "learning" from the data generated by finite element calculation of a set of representative volume elements at cellular scales. This effective strain energy density is then used to predict the mechanical responses of cellular materials at larger scales. Compared with direct finite element simulation, the proposed scheme can reduce the computational time up to two orders of magnitude. Potentially, this scheme can facilitate new optimization algorithms for designing cellular materials of highly specific mechanical properties.